Fitness-to-Drive Screening Measure©: Patterns and Trends for Canadian Users - Sherrilene Classen; Shabnam Medhizadah; Liliana Alvarez (Scholarworks @ WMU, 2016)
Background: The Fitness-to-Drive Screening Measure© (FTDS) is an online screening tool that enables proxy raters (caregivers, family members, and friends) to identify at-risk older adult drivers via 54 driving-related items. This study aimed to identify areas in need of improvement for the FTDS by identifying the patterns and trends of Canadian users and providing recommendations to increase the usage, reach, and potential impact of the FTDS as a health promotion tool. Methods: We used monthly Google Analytics reports to calculate descriptive statistics for web page and session specific variables. Variables were separated into Year 1 and Year 2 and were compared using the independent sample t-test. Results: Patterns were identified for session and web page specific variables; for example, users spent less than the recommended 20 min to complete the FTDS. There was only a significant decrease in the number of French speaking users (t (22) = .01, p < .05) from Year 1 to Year 2. Conclusion: Canadians across the country are able to easily access and use the FTDS for screening older adult drivers in its current format. However, implementing suggested recommendations (e.g., short form FTDS) may increase the overall usage, utility, and/or reach of the FTDS, and, as such, may yield additional benefits to potential users.